DyNamic interactive anticipation-time for a paradigmatic shift - Cañal-Bruland, R.; Mann, D. L. (Sports Medicine, 2025)
Everyday human interactions require observers to anticipate the actions of others (e.g., when walking past another in a corridor or choosing where to hit a ground stroke in tennis). Yet, experimental paradigms that aim to examine anticipation continue to use simplistic designs that are not interactive and therefore fail to account for the real-life, social nature of these interactions. Here we propose a fundamental, paradigmatic shift toward a "dynamic interactive anticipation" paradigm that models real-life interactions. We propose that it will change the way behavioral experimentalists study anticipation and spark theory development by unravelling the mechanisms underlying anticipation in real-time interactions.